Posouzení informačního systému firmy Trios a návrh změn - Staněk, Miroslav (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato práce komplexně analyzuje jednotlivé složky informačního systému firmy Trios. Dále také předkládá možné řešení pro zamýšlenou inovaci IS, které povede ke zefektivnění podnikových procesů a k rozšíření stávající zákaznické základny.

This work analyses in detail the individual components of the information systems of the Trios company. It further introduces possible solutions for the intended innovations in IS, that will lead towards optimisation of business processes and to the expansion of the current customer base.
Review of the information system of company Trios and proposal of changes
Keywords: Informační systém; informační technologie; Information system; infomation technology